Public Administration and the Protection of Private Rights: Questioning Its Recognition and Application Under Ukrainian Law - Oksana Brusakova; Oleksandra Karmaza; Viktor Vasylenko; Vita Moroz (Ius Humani. Jornal do direito, 2022)
Every society needs the recognition and protection of the rights of its citizens, and this becomes more proper for every administration in respecting this protection for the common good of its society. In this article, international experience of protecting private rights in the sphere of public administration has been analyzed. On the basis of the researched information the authors have provided concrete ways of implementing the specified international experience into domestic state and his legal system. The essence and characteristic features of legal ways to protect the legitimate interests of private individuals within public relations have been clarified among other things. The genesis of the development of the ways to protect private rights in the sphere of public administration has been analyzed. Particular attention has been paid to the insufficient capacity of Ukraine to ensure the inviolability of private rights, freedoms and interests of the entities of public legal relations, compared to the developed countries of Western Europe and North America. At the same time, the emphasis has been made on the gradual increase in the level of democracy and the rule of law in Ukraine over the last 20 years. It has been claimed that a special “acceleration” of the indicated reforms took place immediately after two socially important events, namely the Orange Revolution of 2004 and the Revolution of Dignity of 2013-2014. However, the so-called “energy fervor” gained at the beginning of the reform is slowing down in Ukraine.